Native mycorrhizal fungi as growth promoters in guava plants (Psidium guajava L.) - Quiñones-Aguilar, Evangelina Esmeralda; Rincón-Enríquez, Gabriel; López-Pérez, Luis (REVISTA TERRA LATINOAMERICANA, 2020)
This research study assessed the effect of f ive native consortia of arbuscular mycorrhiza on guava (Psidium guajava L.) plant growth. A completely randomized experimental design was established with seven arbuscular mycorrhizal fungus (AMF) treatments named: Las Campesinas (LC), Carlos Rojas (CR), Paso Ancho (PA), El Limón (EL), Cerro del Metate (CM) (native consortia), a commercial strain from the Instituto Nacional de Investigaciones Forestales, Agrícolas y Pecuarias (INIFAP®), and a control group without AMF (w/AMF), in a sterilized sand-soil mixture and under greenhouse conditions. Guava seeds germinated in sterilized sand; the seedlings were subsequently transplanted to a nursery bag with a sterilized sand-soil mixture where they were inoculated with the different AMF treatments. At 125 days after transplant, a destructive sampling was performed, recording plant height, stem diameter, leaf area, and fresh and dry biomass of each part. As variables of plant quality, dry biomass ratio of the aerial part/dry biomass of the root, index of robustness, and Dickson index were determined. The mycorrhizal colonization and spore production in the substrate were determined as microbiological variables. The results showed a differential effect on growth promotion in guava plants when they were inoculated with a native AMF consortium. Among the different consortia evaluated, EL promoted the best guava plant development and quality and where the highest colonization and spore production were reached in the substrate. The plants w/AMF or with the INIFAP inoculum had the highest mortality rate. The colonization percentages were higher than 60%, except for the CM consortium. Therefore, using AMF could be an advisable practice for the sustainable production of guava trees.